Synthesis and Characterization of Cu(II), Cd(II) and Hg(II) Complexes with Schiff Bases - DEMIR, IBRAHIM; AKKAYA, MUSTAFA; BAYRAKCI, MEVLUT; IHSAN PEKACAR, A. (Asian Journal of Chemistry, 2010)
Two new Schiff base have been synthesized by the condensation 1,2-diaminoethane (HL) and 1,4-diamino butane (HL') with isonitroso-p-chloroasetafenon. The complexes of copper(II), cadmium(II) and mercury(II) with HL and HL' were prepared. The ligands and their metal complexes were characterized by spectroscopic techniques.